Long term dento-facial effects of radiotherapy in a treated patient of retinoblastoma - Saba Khan; Sandhya Maheshwari; Mohd Toseef Khan; Sanjeev K. Verma (Elsevier, 2014)
Newer cancer treatment modalities have increased patient survival rate and longevity. Craniofacial and dental abnormalities occurring after radiation therapy and surgery in cancer patients may lead to severe cosmetic or functional sequelae, which may require surgical or orthodontic intervention later on. We, present a case; who was treated for retinoblastoma with enucleation of left eye and external beam radiotherapy at 26 months of age. As a result of radiotherapy there was hypoplasia of the maxilla. This case validates Von-Limborg's theory that states that local epigenetic factor like the developing eye has an important influence on the growth of adjacent structures, as with this patient there was hypoplasia of left orbit. Certain dental anomalies were also seen in the maxillary arch.